2008
DOI: 10.1161/hypertensionaha.107.098186
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Superoxide Dismutase Deficiency Exacerbates Pressure Overload–Induced Left Ventricular Hypertrophy and Dysfunction

Abstract: Abstract-Extracellular superoxide dismutase (SOD) contributes only a small fraction to total SOD activity in the normal heart but is strategically located to scavenge free radicals in the extracellular compartment. To examine the physiological significance of extracellular SOD in the response of the heart to hemodynamic stress, we studied the effect of extracellular SOD deficiency on transverse aortic constriction (TAC)-induced left ventricular remodeling. Under unstressed conditions extracellular SOD deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
104
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 34 publications
10
104
0
2
Order By: Relevance
“…47 Thus it is not surprising that in hypertension the increased production of reactive oxygen species (ROS) is associated with an increased production of peroxynitrite in the heart and coronary blood vessels. 47,48,[73][74][75] The production of peroxynitrite itself has an impact on several pathways of vasodilation including reduced prostaglandin synthesis and inhibition of K + channels. 8,76 Additionally peroxynitrite impairs NO production through oxidation of BH 4 , a NOS co-factor 8,[76][77][78] and also impairs the sGC-mediated response to NO.…”
Section: Nitric Oxide-mediated Vasomotor Function Of Isolated Coronarmentioning
confidence: 99%
“…47 Thus it is not surprising that in hypertension the increased production of reactive oxygen species (ROS) is associated with an increased production of peroxynitrite in the heart and coronary blood vessels. 47,48,[73][74][75] The production of peroxynitrite itself has an impact on several pathways of vasodilation including reduced prostaglandin synthesis and inhibition of K + channels. 8,76 Additionally peroxynitrite impairs NO production through oxidation of BH 4 , a NOS co-factor 8,[76][77][78] and also impairs the sGC-mediated response to NO.…”
Section: Nitric Oxide-mediated Vasomotor Function Of Isolated Coronarmentioning
confidence: 99%
“…16 Echocardiography and Western blots were performed with methods as described previously. 17,18 For details, please see the online data supplement, available at http://hyper.ahajournals.org.…”
Section: Mice and Tac Proceduresmentioning
confidence: 99%
“…4,5) Extracellular-SOD (EC-SOD) is one of the SOD isozymes and plays a pivotal role in the regulation of redox homeostasis, particularly in extracellular spaces. [6][7][8] A previous study reported that the knockdown of EC-SOD exacerbated the progression of atherogenesis through the accumulation of foam cells in the neointima region 9) ; on the other hand, the overexpression of EC-SOD has been shown to suppress atherogenesis. 10) Therefore, maintaining the expression of EC-SOD at high levels in vessel walls may prevent the initiation and progression of vascular diseases.…”
mentioning
confidence: 99%